1975
DOI: 10.1017/s0022029900015399
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between stage of lactation and pregnancy and blood composition in a herd of dairy cows and the influences of seasonal changes in management on these relationships

Abstract: Blood samples, taken on 6 occasions during 1 year from 172 cows resident in a dairy herd, were analysed for packed cell volume, blood glucose, haemoglobin (Hb), serum albumin, urea N, total protein, Ca, inorganic phosphate, Mg, Na and K. The data were analysed statistically, firstly with respect to date of sampling, stage of pregnancy or lactation and the interaction between stage of pregnancy or lactation and date of sampling, and secondly with milk yield as an additional factor for the data for lactating cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
7

Year Published

1976
1976
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 14 publications
5
26
0
7
Order By: Relevance
“…The significant increase in the level of intracellular Na + in the pregnant group (P < 0.001) is comparable to the uniformly observed hypernatraemia during late pregnancy (Kaiser and Cummings, 1958;Rowlands et al, 1975;Kleinman and Lorenz, 1989). This late pregnancy-induced hypernatraem ia maybe as a result of the particularly high aldosterone production, which promotes K + excretion and Na + reabsorption in the renal tubule, during pregnancy (Rowlands et al, 1975).…”
Section: Discussionsupporting
confidence: 79%
“…The significant increase in the level of intracellular Na + in the pregnant group (P < 0.001) is comparable to the uniformly observed hypernatraemia during late pregnancy (Kaiser and Cummings, 1958;Rowlands et al, 1975;Kleinman and Lorenz, 1989). This late pregnancy-induced hypernatraem ia maybe as a result of the particularly high aldosterone production, which promotes K + excretion and Na + reabsorption in the renal tubule, during pregnancy (Rowlands et al, 1975).…”
Section: Discussionsupporting
confidence: 79%
“…Cows milked three times daily had a 6% lower plasma glucose concentration compared with cows milked two times daily (Andersen et al 2004). Albumin, glucose and Hb values decreased in early lactation with increasing the milk yield while calcium and globulin showed the reverse trend (Rowlands et al 1975). In the present study, decrease in Hb was found as reported by earlier workers.…”
Section: Resultssupporting
confidence: 89%
“…3). Esses achados corroboram com os de Rowlands et al (1975), Quayam et al (1990) e Fagliari et al (1998, que encontraram em vacas bovinas e bubalinas uma diminuição não significativa na PPT nas ultimas semanas de gestação. Isso segundo Mulei (1991) é causado principalmente pela transferência de imunoglobulinas do plasma para o colostro.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…Estes achados são similares os verificados por Samak et al (1981), que também encontraram uma diminuição significativa do hematócrito no pós-parto, principalmente no início e meio da lactação de vacas bovinas. Para Rowlands et al (1975) e Jones et al (1982), a produção de leite no pós-parto seria o fator responsável pela diminuição do hematócrito. Porém, Dirksen et al (1993), afirmam que os fatores nutricionais, como a deficiência de proteínas e minerais (ferro, cobre e cobalto) são as principais fatores responsáveis pela diminuição do hematócrito em vacas bovinas em lactação no pós-parto.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified